Origin of α-poor Very Metal-poor Stars - S. K. Jeena; Projjwal Banerjee (The Astrophysical Journal)
Among very metal-poor (VMP) stars, α -poor VMP ( α -PVMP) stars that have subsolar values of [X/Fe] for Mg and other α elements are rare and are thought to have been formed from gas polluted by Type 1a supernova (SN 1a). However, recent analyses indicate that pure core-collapse supernova (CCSN) ejecta can also be a likely source. We perform a detailed analysis of 17 α -PVMP stars by considering six different scenarios relevant to the early Galaxy. We consider a single pair-instability supernova (PISN) and a single CCSN. Additionally, we consider the combination of ejecta from a CCSN with ejecta from another CCSN, a PISN, a near-Chandrasekhar mass (near- M _Ch ) SN 1a, and a sub-Chandrasekhar mass (sub- M _Ch ) SN 1a. A clear signature can only be established for sub- M _Ch SN 1a with a near-smoking-gun signature in SDSS J0018-0939 and a reasonably clear signature in ET0381. The majority (82%) of α -PVMP stars can be explained by pure CCSN ejecta and do not require any SN 1a contribution. However, the combination of CCSN and sub- M _Ch SN 1a ejecta can also explain most (76%) of α -PVMP stars. In contrast, the combination of ejecta from CCSN with near- M _Ch SN 1a and PISN can fit 41% and 29% of the stars, respectively. The single PISN scenario is strongly ruled out for all stars. Our results indicate that α -PVMP stars are equally compatible with pure CCSN ejecta and a combination of CCSN and SN 1a ejecta, with sub- M _Ch SN 1a being roughly twice as frequent as near- M _Ch SN 1a.